2012
DOI: 10.6061/clinics/2012(11)15
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Celsior and Perfadex lung preservation solutions in rat lungs subjected to 6 and 12 hours of ischemia using an ex-vivo lung perfusion system

Abstract: OBJECTIVE:This study evaluated the performance of lungs that were preserved with different solutions (Celsior, Perfadex or saline) in an ex vivo rat lung perfusion system.METHODS:Sixty Wistar rats were anesthetized, anticoagulated and randomized into three groups (n = 20). The rats were subjected to antegrade perfusion via the pulmonary artery with Perfadex, Celsior, or saline, followed by 6 or 12 hours of ischemia (4°C, n = 10 in each group). Respiratory mechanics, gas exchange and hemodynamics were measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Few cells have been observed to have chromatin condensation, which may suggest an early stage of apoptosis. The basement membrane thickness was comparable in both groups (Menezes et al, 2012). However, clinical studies by Gohrbandt et al demonstrated that Celsior protected lungs during transplantation better than Perfadex.…”
Section: Fluids For Rinsing and Storing Organsmentioning
confidence: 86%
“…Few cells have been observed to have chromatin condensation, which may suggest an early stage of apoptosis. The basement membrane thickness was comparable in both groups (Menezes et al, 2012). However, clinical studies by Gohrbandt et al demonstrated that Celsior protected lungs during transplantation better than Perfadex.…”
Section: Fluids For Rinsing and Storing Organsmentioning
confidence: 86%
“…The Pego-Fernandes group reported that their solution, low potassium dextran-glucose (LPDnac) was comparable to Perfadex (Vitrolife, Goteborg, Germany) but found saline to be inadequate [13,14] . Menezes et al [15] also compared Perfadex to Celsior and found lungs perfused with either exhibited similar gas exchange and histopathological findings.…”
Section: Pathway To Evaluate Efficacy Of Experimental Treatmentsmentioning
confidence: 98%
“…Basic properties, such as the optimal electrolyte composition of the perfusate itself are not agreed upon. Current data are unclear as to which currently available solutions perform best [15] . Perfadex, a solution developed specifically for lung preservation, may not offer better preservation than Celsior, a heart preservation solution [15,25] .…”
Section: Overall Advantagesmentioning
confidence: 99%
“…Although 2 studies have confirmed Celsior's ability to provide similar clinical results to those of the Perfadex solution, with additional trends towards better survival and less incidence of chronic lung allograft dysfunction, especially with longer ischemic periods, Perfadex remains the most widely used preservation solution in most lung transplant centers [6,7].…”
Section: State Of the Artmentioning
confidence: 99%